That is a good point we can use its series expansion... WAIT
THE SERIES EXPANSION!!!
We can use it to maybe SOLVE THE INTEGRAL (in series form BUT WHO CARES)!!!
\[\frac { 1 }{ 1+x } =1-x+{ x }^{ 2 }-{ x }^{ 3 }+{ x }^{ 4 }-...=\sum _{ n=0 }^{ \infty }{ { (-1) }^{ n }{ x }^{ n } } \]
\[\frac { 1 }{ 1+{ x }^{ 2 } } =1-{ x }^{ 2 }+{ x }^{ 4 }-{ x }^{ 6 }+{ x }^{ 8 }-...=\sum _{ n=0 }^{ \infty }{ { (-1) }^{ n }{ x }^{ 2n } } \]
\[\frac { 1 }{ 1+{ x }^{ 3 } } =1-{ x }^{ 3 }+{ x }^{ 6 }-{ x }^{ 9 }+{ x }^{ 12 }-...=\sum _{ n=0 }^{ \infty }{ { (-1) }^{ n }{ x }^{ 3n } } \]
So:
\[\frac { 1 }{ 1+{ x }^{ k } } =1-{ x }^{ k }+{ x }^{ 2k }-{ x }^{ 3k }+{ x }^{ 4k }-...=\sum _{ n=0 }^{ \infty }{ { (-1) }^{ n }{ x }^{ kn } } \]
and...:
\[\int { \frac { 1 }{ 1+{ x }^{ k } } dx } =\int { (1-{ x }^{ k }+{ x }^{ 2k }-{ x }^{ 3k }+{ x }^{ 4k }-...)dx } =\int { \sum _{ n=0 }^{ \infty }{ { (-1) }^{ n }{ x }^{ kn } } dx } \]

Simplifying the integral of the right: (Not including the +C in the integral)
\[\int { \sum _{ n=0 }^{ \infty }{ { (-1) }^{ n }{ x }^{ kn } } dx } =\sum _{ n=0 }^{ \infty }{ \int { { (-1) }^{ n }{ x }^{ kn }dx } } =\sum _{ n=0 }^{ \infty }{ \frac { { (-1) }^{ n }{ x }^{ kn+1 } }{ kn+1 } } =x-\frac { { x }^{ k+1 } }{ k+1 } +\frac { { x }^{ 2k+1 } }{ 2k+1 } -\frac { { x }^{ 3k+1 } }{ 3k+1 } +\frac { { x }^{ 4k+1 } }{ 4k+1 } -...\]
... which is so far all the work that can be done, without using any special functions.

Thus:
\[\int { \frac { 1 }{ 1+{ x }^{ k } } dx } =\sum _{ n=0 }^{ \infty }{ { \frac { { (-1) }^{ n }{ x }^{ kn+1 } }{ kn+1 } } } \]
Done

Just glancing at it and some solutions computed with WolframAlpha, it looks like you have to use partial fractions to decompose it and then integrate term-by-term, which makes me unsure about whether or not a closed-form solution exists...

Integrate term by term... that is correct. In fact, the terms you need to integrate are actually very surprising.. x^n and -x^k! The answer is that \(\int { \frac { 1 }{ 1+{ x }^{ k } } dx } =\sum _{ n=0 }^{ \infty }{ { \frac { { (-1) }^{ n }{ x }^{ kn+1 } }{ kn+1 } } } \)!

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestOk......What if someone replaces the + sign with a - sign........Can we solve it and generalize it??

Log in to reply

That is a good point we can use its series expansion... WAIT THE SERIES EXPANSION!!! We can use it to maybe SOLVE THE INTEGRAL (in series form BUT WHO CARES)!!! \[\frac { 1 }{ 1+x } =1-x+{ x }^{ 2 }-{ x }^{ 3 }+{ x }^{ 4 }-...=\sum _{ n=0 }^{ \infty }{ { (-1) }^{ n }{ x }^{ n } } \] \[\frac { 1 }{ 1+{ x }^{ 2 } } =1-{ x }^{ 2 }+{ x }^{ 4 }-{ x }^{ 6 }+{ x }^{ 8 }-...=\sum _{ n=0 }^{ \infty }{ { (-1) }^{ n }{ x }^{ 2n } } \] \[\frac { 1 }{ 1+{ x }^{ 3 } } =1-{ x }^{ 3 }+{ x }^{ 6 }-{ x }^{ 9 }+{ x }^{ 12 }-...=\sum _{ n=0 }^{ \infty }{ { (-1) }^{ n }{ x }^{ 3n } } \] So: \[\frac { 1 }{ 1+{ x }^{ k } } =1-{ x }^{ k }+{ x }^{ 2k }-{ x }^{ 3k }+{ x }^{ 4k }-...=\sum _{ n=0 }^{ \infty }{ { (-1) }^{ n }{ x }^{ kn } } \]

and...:\[\int { \frac { 1 }{ 1+{ x }^{ k } } dx } =\int { (1-{ x }^{ k }+{ x }^{ 2k }-{ x }^{ 3k }+{ x }^{ 4k }-...)dx } =\int { \sum _{ n=0 }^{ \infty }{ { (-1) }^{ n }{ x }^{ kn } } dx } \]Simplifying the integral of the right: (Not including the +C in the integral) \[\int { \sum _{ n=0 }^{ \infty }{ { (-1) }^{ n }{ x }^{ kn } } dx } =\sum _{ n=0 }^{ \infty }{ \int { { (-1) }^{ n }{ x }^{ kn }dx } } =\sum _{ n=0 }^{ \infty }{ \frac { { (-1) }^{ n }{ x }^{ kn+1 } }{ kn+1 } } =x-\frac { { x }^{ k+1 } }{ k+1 } +\frac { { x }^{ 2k+1 } }{ 2k+1 } -\frac { { x }^{ 3k+1 } }{ 3k+1 } +\frac { { x }^{ 4k+1 } }{ 4k+1 } -...\] ... which is so far all the work that can be done, without using any special functions.

Thus: \[\int { \frac { 1 }{ 1+{ x }^{ k } } dx } =\sum _{ n=0 }^{ \infty }{ { \frac { { (-1) }^{ n }{ x }^{ kn+1 } }{ kn+1 } } } \] Done

Log in to reply

@Pepper Mint Well, we can solve this sort of definite integral ranging from 0 to infinity.........this is simply using Beta function....!!!

Log in to reply

But it won't help solve for the indefinite integral. hmm

Log in to reply

Anyway, we know that: \[\int { \frac { 1 }{ 1+{ x } } } dx=\ln { (1+x) } +C\] and \[\int { \frac { 1 }{ 1+{ x }^{ 2 } } } dx=\arctan { x } +C\]

but\[\int { \frac { 1 }{ 1+{ x }^{ 3 } } } dx\] is a mess...(Just in case you don't believe me): \[\int { \frac { 1 }{ 1+{ x }^{ 3 } } } dx=-\frac { \ln { |{ x }^{ 2 }-x+1| } -2(\ln { |x+1| } +\sqrt { 3 } \arctan { (\frac { 2x-1 }{ \sqrt { 3 } } ) } ) }{ 6 } +C\]

Log in to reply

Just glancing at it and some solutions computed with WolframAlpha, it looks like you have to use partial fractions to decompose it and then integrate term-by-term, which makes me unsure about whether or not a closed-form solution exists...

Log in to reply

Integrate term by term... that is correct. In fact, the terms you need to integrate are actually very surprising.. x^n and -x^k! The answer is that \(\int { \frac { 1 }{ 1+{ x }^{ k } } dx } =\sum _{ n=0 }^{ \infty }{ { \frac { { (-1) }^{ n }{ x }^{ kn+1 } }{ kn+1 } } } \)!

Log in to reply

You can see the power rule in the summation!

Log in to reply

Comment deleted 3 months ago

Log in to reply

This doesn't help!! We need another approach

Log in to reply

But how to use this, I mean without substitution can we have a direct approach?

Log in to reply